The cultural differences in transition assessment: Evaluation of TRANSITION-Q and STARx scales on Turkish rheumatic patients - Ramazan Emre Yiğit; Şengül Çağlayan; Betül Sözeri (Archives of Rheumatology, 2024)
Objectives: This study aimed to assess the readiness of our patient population for the transfer to adult care and the applicability of the TRANSITION-Q and STARx scales to the Turkish adolescent patient population. Patients and methods: A total of 153 patients (92 males, 61 females; mean age: 15.5±1.9 years; range, 12 to 18 years) were included in the study between September 15, 2021, and December 15, 2021. The patients were divided into two groups according to age groups: 12 to 15 years old and 16 to 18 years old. The patients were also divided into four groups according to their diagnosis: connective tissue diseases, juvenile idiopathic arthritis, vasculitis, and autoinflammatory diseases. The TRANSITION-Q and STARx scales were administered face-to-face by a nurse and a doctor. The transition readiness of the patients was evaluated according to their scores. Results: Sixty-nine (45%) patients were in the 12 to 15 age group, and 84 (55%) were in the 16 to 18 age group. Eight-four (54.9%) patients had juvenile idiopathic arthritis, 47 (30.7%) patients had an autoinflammatory disease, 14 (9.2%) patients had vasculitis, and eight (5.2%) patients had a connective tissue disease. There was no significant difference in the scale scores according to disease groups and sexes in both scales. Considering the age of the patients, the mean scores of the patients in the 16 to 18 age group were found to be significantly higher compared to the 12 to 15 age group for both the TRANSITION-Q (74.3±13.3 vs. 65.4±9.6, p<0.001) and STARx scales (51.8±8.1 vs. 44.8±9.1, p<0.001). Cronbach’s alpha score was 0.71 for the STARx scale and 0.79 for the TRANSITION-Q scale. Conclusion: TRANSITION-Q and STARx scales could guide the Turkish patient population in determining the pretransition needs of patients in planning individualized transition processes.